The trial of Emma Cunningham : murder and scandal in the Victorian era - Jenkins, Brian (Brian A.) (McFarland & Company, Inc., Publishers, 2020)
"The alleged 1857 murder of a wealthy Bond Street dentist by a Emma Cunningham, a young widow he was believed to be sexually involved with, served to distract many New Yorkers from the deepening national crisis over slavery in the United States. Public anxieties seemed well founded-domestic murders committed by women were believed to be increasing sharply, jeopardizing society's patriarchal structure. The penny press created public demand for a swift solution. The inadequacy of the city police, complicated by the state's decision to install a new force, resulted in the rival forces battling it out on the streets. Elected coroners conducting inquests and elected D.A.'s prosecuting alleged culprits fed a tendency to rush to judgment. New York juries, all men, were reluctant to send a middle class woman to the gallows. At trial, Cunningham proved a formidable and imaginative member of the so-called weaker sex and was acquitted. This reexamination places the story in its social and political context."--